A Comparative Evaluation of Various Therapies of Synthetic Drugs with Amla and Honey Combination for the Treatment of Gastroesophageal Reflux Disease - Mazumder, Avijit; Kumar, Naveen; Das, Saumya (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Gastroesophageal Reflux Disease (GERD) is disorder of oesophagus that causes ulcer and erosion. Materials and Methods: A comparison based on the in vivo study was carried out to determine the therapeutic efficacy of herbal formulation using Amla and Honey in combination with Pantoprazole and Rebamipide for the treatment of GERD. The effects of all above mentioned medications were also checked on intestinal motility. In vitro studies were carried out to determine the antispasmodic activity of Amla and Honey in comparison to acetylcholine by isolated rat ileum. In pylorus ligation GERD model, mono-therapy was performed by giving herbal formulation of Amla and Honey. In combination therapy Pantoprazole and Rebamipide, Amla and Honey with Pantoprazole and Rebamipide were given and their therapeutic efficacy was observed at the ends of 14 days. In charcoal meal motility test the distance travelled by charcoal in intestine was measured. Results and Discussion: Combination therapy have highest therapeutic efficacy in comparison to mono-therapy of natural combination of Amla and Honey against Pantoprazole and Rebamipide. In vitro antispasmodic activity revealed that Amla and Honey formulation decreased the contractility pattern in concentration dependent manner against acetylcholine. In charcoal meal motility test highest intestinal motility were observed in Amla and Honey and can be given in GERD for easily digestion of food from stomach. Conclusion: Herbal combination of Amla and Honey in comparative evaluation decreases the Gastroesophageal reflux disease, intestinal mobility, and show anti-spasmodic activity in isolated rat’s ileum. However, these combinations serve as a more potential agent for decreasing all the factors responsible for the reflux disease.
Keywords: Combination therapy; Mono-therapy; Pantoprazole; Rebamipide; Mucosal